2007
DOI: 10.1038/sj.ijo.0803622
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of infant feeding and obesity throughout life course

Abstract: We did not find that having been breastfed was associated with women's likelihood of becoming overweight or obese throughout life course. Although breastfeeding promotes the health of mother and child, it is unlikely to play an important role in controlling the obesity epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 32 publications
6
89
1
4
Order By: Relevance
“…The later obesity appears, the more it persists. In fact, as in other studies [11][12][13], we found that childhood characteristics (the weight at birth, at age 5, and at age 10) contribute significantly to adolescents' overweight and obesity. However, the effect of obesity at puberty is more obvious, since this period is associated with many metabolic and hormonal changes that promote fat gain [2] and the risk of obesity and its related disorders [1].…”
Section: Obesity-related Parameterssupporting
confidence: 72%
See 2 more Smart Citations
“…The later obesity appears, the more it persists. In fact, as in other studies [11][12][13], we found that childhood characteristics (the weight at birth, at age 5, and at age 10) contribute significantly to adolescents' overweight and obesity. However, the effect of obesity at puberty is more obvious, since this period is associated with many metabolic and hormonal changes that promote fat gain [2] and the risk of obesity and its related disorders [1].…”
Section: Obesity-related Parameterssupporting
confidence: 72%
“…Concerning this point, our results obviously differ from several previous studies which concluded that breast-feeding, for more than 4 or 6 months, is associated with lower rates of obesity [13,29], and with a leaner body shape during childhood (5 years old) [11,30]. Indeed, we found more overweight and obese adolescents who were breastfed for a long period (exceeding 9 or 12 months) compared with those of normal weight.…”
Section: Obesity-related Parameterscontrasting
confidence: 56%
See 1 more Smart Citation
“…Some studies have found a positive, dose-dependent association between breastfeeding and weight status (11)(12)(13) , while others have reported a nonlinear positive response (14)(15)(16) . On the contrary, other studies have demonstrated little or no protective association between breastfeeding and overweight; including a longitudinal study of infant feeding and obesity which found that exclusive breastfeeding was not related to being overweight or obese during adult life (17)(18)(19)(20)(21) . Similarly, a systematic analysis conducted by the WHO (22) and a systematic review of the literature found that after adjustment for maternal overweight the effect of breastfeeding was eliminated (23) .…”
mentioning
confidence: 92%
“…Both duration of exclusive breastfeeding and breastfeeding in general are often used in obesity studies as potential protective factors regarding overweight and obesity in childhood. 7,20 The inconsistency of the findings regarding the repeatability of parental report on breastfeeding 10,12,21 might be contributing to the controversial discussion regarding the protective effect of breastfeeding on overweight and obesity in childhood. 7,20,22 Several studies suggested that the repeatability of maternal reports on breastfeeding is likely to be poorer if the question is asked at an older age.…”
Section: S56mentioning
confidence: 99%